Endoscopic transpapillary stent placement in patients with necrotizing pancreatitis and disconnected main pancreatic duct syndrome - Shabunin, Aleksey V.; Bagatelia, Zurab A.; Bedin, Vladimir V.; Korzheva, Irina Yu; Shikov, Dmitry V.; Kolotilshchikov, Andrei A.; Kalashnikova, Elena A.; Covantsev, Serghei (Frontiers in Surgery, 2023)
Introduction Pancreatic necrosis is one of the most severe acute abdominal conditions, accounting for 15%–20% of all patients with acute pancreatitis and characterized by significant rates of postoperative complications and mortality. Patients with pancreatic necrosis, in which pathological changes are localized in the proximal pancreas and retroperitoneal space, deserve special attention. This form of the disease includes patients with disconnected main pancreatic duct (MPD) syndrome who have a difficult prognosis. Aim The aim of the study was an improvement of treatment results in patients with necrotizing pancreatitis and signs of the dissociation of the pancreas duct system using the endoscopic transpapillary stent placement method. Material and methods This study was a retrospective cohort study. There were 32 patients with acute necrotizing pancreatitis who were managed using the endoscopic transpapillary stent placement method between 2019 and 2021. Disconnected MPD syndrome was diagnosed in all 32 patients. In total, 26 patients were admitted to hospital in the first 72 h, while 6 patients were admitted after 72 h. We diagnosed the necrotizing process located in the proximal and central areas of the pancreas and peripancreatic space in all these patients (“model III”). Results Positive results related to transpapillary stent placement were noted in 24 (75%) patients (first cohort). A total of 20 patients from this group were admitted to hospital in the first 48 h, and 4 patients were admitted later than 72 h from the onset of disease. Moreover, 8 patients (25%; second cohort) failed to succeed in transpapillary stent placement. Complications in the first cohort occurred in 3 (12.5%) patients: dislocation of the stent into the duodenum occurred in 1 patient, and bleeding after papillosphincterotomy took place in 2 patients. Meanwhile, infected necrotized pancreatitis developed in 5 patients, and 1 patient (5%) died. Complications among the second cohort occurred in 2 (25%) patients: erosive bleeding (after debridement). Infected necrotized pancreatitis developed in 4 patients, and 2 patients (25%) died. Conclusions Endoscopic transpapillary stent placement is an effective minimally invasive approach in the management of patients with necrotizing pancreatitis.